Analysis of the Effect of Fiscal Policy on Regional Economic Growth in South Sulawesi - Jam’an Jam’an (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect of fiscal policy on regional economic growth in South Sulawesi. This research uses quantitative descriptive research. The analytical model used to quantify the effect of changing fiscal policy on regional economic development is panel regression analysis, which employs three distinct approaches: fixed effect, random effect, and standard effect. According to the data analysis, fiscal policy instruments on the revenue side have varying effects on economic growth in South Sulawesi. Local taxes have a substantial beneficial effect on economic growth, while the results of local taxes have a significant negative effect on economic growth. Valuable fiscal policy regarding government spending shows that spending on grants, social assistance, and goods and services positively and significantly impacts economic growth. At the same time, the capital expenditure variable has a positive but not significant effect.